TINDAK TUTUR RIDWAN REMIN PADA STAND UP COMEDY INDONESIA SEASON 7 KOMPAS TV EDISI JUNI 2017 - Tilsep Jasnain (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
The problem of this research is what are Ridwan Remin's speech acts in the June 2017 edition of Stand Up Comedy Indonesia, Kompas TV. The purpose of this study is to find out and describe Ridwan Remin's speech acts in his appearance in Stand Up Comedy which specializes in locus speech acts, illocution and perlocution. The method used in this research is descriptive qualitative method. The data source and the object of the research were the videos of Ridwan Remin's Stand Up Comedy performance at the Stand Up Comedy Indonesia season 7, Kompas TV June 2017 edition, consisting of 5 videos. Data analysis techniques are using documentation techniques. The analysis results obtained are in the form of 20 sentences of speech action locus, 10 sentences of speech acts of illocution, and 3 sentences of speech acts of perlocution. In speech, of course, speech acts are needed so that the meaning in the speech can be conveyed to the speech partner so that it can cause a reaction or reciprocal relationship for the speaker.